South African land reform as peacebuilding: integrating perspectives from social identity theory and symbolic politics in a peacebuilding conceptual framework - Young, Gert (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.